A comparative investigation of different cooling media on the FSW joints of AA6061-T651 alloy - A. Ugla, Adnan; I. Radhi, Hazim; S. Faisal, Ahmed (International Journal of Engineering and Technology, 2018)
The present work aims to compare the effect of different cooling media namely, air, water and oil on the characteristics of the welded part of the AA606-T651 alloy using friction stir welding. The results showed that the welded part quality is much improved using the proposed immersed media (oil). However, the tensile strength and the ductility of the joined parts significantly increase using oil submerged friction stir welding process. Whereas, the impact energy was slightly more than that of the air submerged friction stir welding and slightly less than that of the conventional friction stir welding.Â